2004
DOI: 10.1007/s11005-004-4072-2
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Sufficient Quantum Coarse-Grainings

Abstract: Let H and K be finite dimensional Hilbert spaces, T : B(H) → B(K) be a coarse-graining and D 1 , D 2 be density matrices on H. In this paper the consequences of the existence of a coarse-graining β :H (p) (s = 1, 2) should hold with pairwise orthogonal summands and with commuting factors and with some probability distributions λ s (p) for 1 ≤ p ≤ r (s = 1, 2). This decomposition allows to deduce the exact condition for equality in the strong subaddivity of the von Neumann entropy.Mathematics Subject Classifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…One can extend this notion to that of a sufficient channel (or sufficient stochastic map), as discussed in [Pet86b,Pet88,MP04,Mos05]. A channel T ≡ T Y |X is sufficient for two input distributions p X and q X if there exists another channel (a recovery channel ) such that both these inputs can be recovered perfectly by sending the outputs of the channel T Y |X corresponding to them through it.…”
Section: I(x; Z|y ) ≡ H(xy ) + H(zy ) − H(y ) − H(xy Z)mentioning
confidence: 99%
“…One can extend this notion to that of a sufficient channel (or sufficient stochastic map), as discussed in [Pet86b,Pet88,MP04,Mos05]. A channel T ≡ T Y |X is sufficient for two input distributions p X and q X if there exists another channel (a recovery channel ) such that both these inputs can be recovered perfectly by sending the outputs of the channel T Y |X corresponding to them through it.…”
Section: I(x; Z|y ) ≡ H(xy ) + H(zy ) − H(y ) − H(xy Z)mentioning
confidence: 99%
“…The case of equality was studied in several papers recently but always restricted to finite dimensional Hilbert spaces [7,10]. Our aim now is to allow infinite dimensional spaces.…”
Section: Exponential Familiesmentioning
confidence: 99%
“…Equality in the strong subadditivity is equivalent to sufficiency of the subalgebra B(H A ⊗ H B ) ⊗ C1 C for (B(H), S) where S := {ω ABC , ω A ⊗ ω BC }, and the latter is equivalent to The structure (29) of the density matrix ω ABC is similar to the finite dimensional situation discussed in [7,10], however the direct sum decomposition may be infinite.…”
Section: Theoremmentioning
confidence: 99%
“…4 It has been shown that the Markov property is tightly related to the sufficiency of conditional expectations through the strong subadditivity of von Neumann entropy: A state of a threecomposed tensor-product system is Markovian if and only if it takes the equality for the strong subadditivity inequality of entropy, which will be referred to as "the strong additivity of entropy." 16,6,12,7 We show that a similar equivalence relation of the Markov property and the strong additivity of entropy is valid for graded quantum systems. Its proof proceeds in much the same way as that for the tensor-product case following Ref.…”
Section: Introductionmentioning
confidence: 68%